2022
DOI: 10.3390/app12052400
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-Shape Discrimination of SiPM Array-Coupled CLYC Detector Using Convolutional Neural Network

Abstract: Cs2LiYCl6: Ce3+ (CLYC) is a dual-mode gamma-neutron scintillator with a medium gamma-ray resolution and pulse-shape discrimination (PSD) capability. The PSD performance of CLYC is greatly weakened when coupled with silicon photomultipliers (SiPMs) because of SiPMs’ low detection efficiency for the ultrafast Core-Valence-Luminescence (CVL) component under gamma excitation. In our previous work, the PSD Figure-of-Merit (FoM) value was optimized to 2.45 at the gamma-equivalent energy region of the thermal neutron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although the SiPM gain is greater after the bias correction in the high-temperature section, the SiPM dark count also increases when the bias is increased, so the overall SNR difference is not significant. In general, there is little difference in the FOM of the detector before and after bias correction, and the deviation is less than 2.4% in the range 0-50 • C. Previous studies have shown that NaIL containing 1% 6 Li has obvious differences in the shapes and speed composition of neutron and gamma pulses at different temperatures [16]. Obtaining the optimal FOM requires adjusting the screening parameters of the PSD algorithm.…”
Section: Psd Parameter Correction Based On Temperature Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the SiPM gain is greater after the bias correction in the high-temperature section, the SiPM dark count also increases when the bias is increased, so the overall SNR difference is not significant. In general, there is little difference in the FOM of the detector before and after bias correction, and the deviation is less than 2.4% in the range 0-50 • C. Previous studies have shown that NaIL containing 1% 6 Li has obvious differences in the shapes and speed composition of neutron and gamma pulses at different temperatures [16]. Obtaining the optimal FOM requires adjusting the screening parameters of the PSD algorithm.…”
Section: Psd Parameter Correction Based On Temperature Feedbackmentioning
confidence: 99%
“…Pulse shape discrimination is mainly used in scintillator detectors such as plastic scintillators, liquid scintillators, and inorganic scintillators. Systems using CLYC are well known in current studies of neutron-gamma detection [6]. As a new type of inorganic scintillator for neutron-gamma detection, NaIL has the advantages of low production cost, high thermal neutron detection efficiency, and good neutron-gamma discrimination [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has the advantages of stability, reliability and simplicity in computation along with a high discrimination power [11]. It is considered as a reference to compare with more recent algorithms of neutron/gamma discrimination that have been recently proposed, such as the use of convolutional neural networks [12].…”
Section: Introductionmentioning
confidence: 99%